Circular economy and 3D printing in the healthcare sector - Mansour, Nada Khaled; Callera, Arianna; Potere, Federica; Micalizzi, Simone; Costantino, Maria Laura; De Gaetano, Francesco; Oliva, Paolo (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionIn the last decades, 3D printing has demonstrated its potential across various sectors, including healthcare. However, there remains a notable gap in the integration of circular economy principles to recycle plastic waste into functional, high-quality 3D printing filaments, particularly in clinical settings. This work addresses this gap by exploring the sustainability of 3D printing in healthcare through the recycling of plastic waste into 3D printable filaments.MethodsThe process involves the collection, shredding, extrusion, and spooling of high-density polyethylene (HDPE) water bottle caps, collected from hospital setting. Key steps, such as extrusion and printing processes, were optimised, and the mechanical properties of the filament were thoroughly assessed. An economic and an environmental impact analysis was also conducted to evaluate the overall process. Optimization of each phase of the circular economy process led to the production of a functional recycled filament, with homogeneous diameter and surface finish quality.ResultsDespite HDPE being challenging to print, targeted adjustments significantly enhanced the print quality. The study not only aimed to obtain a usable filament but also to assess the economic and environmental impact of the whole process. The results indicated cost saving from in-house filament production compared to commercial options and a notable reduction in the environmental impact measured in carbon dioxide (CO2) emission equivalent. The recycled filament was successfully used to print a patient-specific anatomical model of an intracranial aneurysm, as a support for surgical planning.DiscussionThis demonstrates the feasibility of integrating sustainable 3D printing practices in healthcare, offering economics and environmental benefits while enhancing clinical support.